MicroRNAs regulate alveolar macrophage homeostasis and its function in lung fibrosis - Parajuli, Nirmal; Yao, Yi; Khalasawi, Namir; Yin, Congcong; Zhang, Qiong; Adrianto, Indra; Hans, Aakash; Zhou, Li; Mi, Qing-Sheng (Frontiers in Immunology, 2025)
IntroductionIdiopathic pulmonary fibrosis is a progressive lung disease with a poor prognosis. Alveolar macrophages (AMs) are essential for maintaining lung homeostasis and play a significant role in the development of lung fibrosis. Tissue-Resident Alveolar Macrophages (TR-AMs), which originate from embryonic progenitors, can self-renew locally in a steady state, independent of hematopoiesis. During fibrogenesis, circulating monocytes rapidly migrate into the lungs and differentiate into monocyte-derived AMs (Mo-AMs). MicroRNAs (miRNAs), small non-coding RNAs, are critical for regulating gene expression. Our recent study found that the loss of miRNAs in embryonic progenitors significantly decreased the number of TR-AMs in late-stage embryos, indicating that miRNAs are necessary for TR-AM development. However, the role of miRNAs in the postnatal maintenance of TR-AMs and Mo-AMs, as well as their function in pulmonary fibrosis, remains unclear.Methods and ResultsHere, we demonstrate that deleting miRNAs after birth severely disrupts TR-AM homeostasis and Mo-AM repopulation from the bone marrow following irradiation. The deficiency of miRNAs in TR-AMs and Mo-AMs was linked to diminished bleomycin-induced experimental lung fibrosis. Mechanistically, the absence of miRNAs increased TR-AM apoptosis under both normal and fibrotic conditions. RNA sequencing (RNA-seq) analysis revealed distinct transcriptomic and pathway changes in miRNA-deficient AM subgroups after lung injury. The integration of RNA-seq and miRNA array analyses identified miRNA-mRNA networks in TR-AMs and Mo-AMs in response to bleomycin injury. Ingenuity Pathway Analysis further predicted let-7a, miR-155, and miR-125 as unique upstream regulators of Mo-AM responses to lung fibrosis.ConclusionsOur findings suggest that miRNAs are key epigenetic mediators that differentially regulate the maintenance and function of TR-AMs and Mo-AMs in the pathogenesis of pulmonary fibrosis.